Birthing parent adverse childhood experiences and risk of atopic diseases in 5-year-old children - Makayla Freeman; Makayla Freeman; Anna L. MacKinnon; Anna L. MacKinnon; Mark Anselmo; Mark Anselmo; Suzanne Tough; Suzanne Tough; Suzanne Tough; Lianne Tomfohr-Madsen (Frontiers in Allergy)
Following up on previous findings from the All Our Families (AOF) cohort, the current study investigated the relationship between birthing parent history of adverse childhood experiences (ACEs) and child atopy, including asthma, allergy, and eczema, at five years of age. Potential indirect effects were explored. Participants completed the ACEs scale, validated questionnaires of anxiety and depression symptoms, and reported on their and their children's atopic disease history. Archival analyses of AOF data (N = 3,387) was conducted using logistic regression and path analysis with counterfactually based indirect effects. Birthing parent history of ACEs was associated with an 18% increased risk of child allergy at five years (OR = 1.18, 95% CI: 1.09, 1.20). Exploratory path analyses indicated a significant indirect effect of ACEs through birthing parent history of atopy on child asthma, allergy, and eczema at five years. There were no significant indirect effects through birthing parent symptoms of anxiety or depression during pregnancy, at two or five years postpartum. Birthing parent history of ACEs, combined with birthing parent history of atopy, may elevate the risk of child atopy. This presents an opportunity for early intervention for children at risk of atopic disease.